W. Va. Code, ch. 153, §8 - (:unkn) unknown (General Publisher, 1870)
Prohibited any person going armed with a deadly or dangerous weapon, without reasonable cause to fear violence. Individuals accused may be required to post a surety.
--
Keywords: CARRY